2020
DOI: 10.3390/plants9040445
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Response to Water Deficit Reveals a Crucial Role of Phosphate Acquisition in a Drought-Tolerant Common Bean Landrace

Abstract: Drought is one of the most critical factors limiting legume crop productivity. Understanding the molecular mechanisms of drought tolerance in the common bean is required to improve the yields of this important crop under adverse conditions. In this work, RNA-seq analysis was performed to compare the transcriptome profiles of drought-stressed and well-irrigated plants of a previously characterized drought-tolerant common bean landrace. The analysis revealed responses related with the abscisic acid signaling, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…In a previous study, several genes of the core ABA signaling were found to change in response to drought in the highly resistant PHA-0683 landrace [ 47 ]. To elucidate whether similar ABA-mediated responses take place in the PMB-0220 line, levels of relative expression of key genes for ABA synthesis (9-Cisepoxycarotenoid Dioxygenase, NCED), degradation ((+)-Abscisic acid 8’-Hydroxylase, ABA 8’H), ABA signaling (type 2C protein phosphatases, PP2Cs) and downstream responsive genes, as the proline synthesis (∆1-Pyrroline–5-Carboxylate Synthase, P5CS), were measured in samples of the two genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, several genes of the core ABA signaling were found to change in response to drought in the highly resistant PHA-0683 landrace [ 47 ]. To elucidate whether similar ABA-mediated responses take place in the PMB-0220 line, levels of relative expression of key genes for ABA synthesis (9-Cisepoxycarotenoid Dioxygenase, NCED), degradation ((+)-Abscisic acid 8’-Hydroxylase, ABA 8’H), ABA signaling (type 2C protein phosphatases, PP2Cs) and downstream responsive genes, as the proline synthesis (∆1-Pyrroline–5-Carboxylate Synthase, P5CS), were measured in samples of the two genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…From these, landrace PHA-0683 ranked as a highly drought-resistant genotype, whereas PMB-0220 was a commercial high yielding line, that ranked as moderately resistant to drought conditions [ 39 ]. In a recent genome wide transcriptomic analysis in leaf tissue of PHA-0683 landrace, differential expression of key genes related with ABA-mediated responses and the regulation of senescence by drought was observed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S6) by drought stress is in agreement with several studies. For instance, a drought-tolerant common bean known as PHB-0683 has been found to change the expression of the cell wall or extracellular proteins in response to water-stress, suggesting that drought caused important changes in the cell wall structure in the common bean plant [ 68 ]. Another drought-tolerant common bean variety, known as BAT 477, has also been analyzed at the transcriptional level under drought conditions [ 69 ].…”
Section: Discussionmentioning
confidence: 99%